PELATIHAN PEMBUATAN SOAL BERBASIS KOMPUTER DENGAN MENGGUNAKAN WONDERSHARE QUIZ CREATOR - Farman Farman (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Evaluation of learning carried out by teachers of SMP Negeri 1 Tinondo so far is still conventional and has not touched the maximum use of technology. Limited knowledge about technology-based learning and evaluation causes teachers to be less innovative and creative in carrying out learning and assessment. In addition, this is also because teachers think that the use of technology in learning and evaluation is quite difficult. In this regard, it is necessary to conduct training for SMP Negeri 1 Tinondo teachers so that they have knowledge and skills in using information technology in learning evaluation. The purpose of this training is for teachers to have information technology knowledge and skills in learning evaluation so that the assessment of learning outcomes is more effective and efficient. The method of implementing this activity consists of four stages, namely: (1) preliminary analysis, (2) preparation, (3) implementation and (4) evaluation. The results of the training showed that the teachers of SMP Negeri 1 Tinondo had understood and were able to compile computer-based evaluation questions using the wondershare quiz creator